2018
DOI: 10.3389/fphar.2018.01404
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Novel Synthetic Analogs in Cell-Based Studies of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a chronic neurodegenerative disorder that is associated with the most common type of dementia and is characterized by the presence of deposits of the protein fragment amyloid beta (Aβ) in the brain. The natural product mixture of curcuminoids that improves certain defects in innate immune cells of AD patients may selectively enhance Aβ phagocytosis by alteration of gene transcription. In this work, we evaluated the protective effects of curcuminoids in cells from AD patients by inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…In this paper, we report a whole transcriptome profiling of both long non-coding and coding RNAs in peripheral blood mononuclear cells (PBMCs) of unmutated SALS) patients [ 24 ], unmutated sporadic AD patients, unmutated sporadic PD patients, and matched controls. PBMCs were chosen as they have been reported to be source of protein and nucleic acid biomarkers in neurodegenerative disorders, also allowing for their use as cellular models for these diseases [ 24 , 25 , 26 , 27 ]. After transcriptome analysis, we focused on the identification of possible crossroads or deviations in the dysregulated pathways of AD, PD, and ALS.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report a whole transcriptome profiling of both long non-coding and coding RNAs in peripheral blood mononuclear cells (PBMCs) of unmutated SALS) patients [ 24 ], unmutated sporadic AD patients, unmutated sporadic PD patients, and matched controls. PBMCs were chosen as they have been reported to be source of protein and nucleic acid biomarkers in neurodegenerative disorders, also allowing for their use as cellular models for these diseases [ 24 , 25 , 26 , 27 ]. After transcriptome analysis, we focused on the identification of possible crossroads or deviations in the dysregulated pathways of AD, PD, and ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Etherification of the hydroxyl groups, on both aromatic rings, showed a higher anti-inflammatory activity. Gagliardi et al [80] showed that treatment with curcuminoids, in a cell model PBMC (peripheral blood mononuclear cells, Supplementary Data), inhibited the activation of inflammation. AB14 showed the most potent protective activity decreasing levels of NF-κB and BACE1 and the inflammatory cascade in cells from AD patients (Figure 1).…”
Section: Anti-neuroinflammatory Activitymentioning
confidence: 99%
“…The results of many studies may be relevant to the use of curcuminoids and vitamin D3 in the prevention of neurodegenerative diseases, which are substances that work via antioxidant and anti-inflammatory mechanisms ([ 179 ] Figure 1 ). Indeed, morbidities of aging have been related to defective functions of both T cells and macrophages leading to brain amyloidosis and inflammation [ 180 ].…”
Section: Neurogenesis Is Stimulated By Vitamin D Metabolites and Smentioning
confidence: 99%
“…“Inflammaging” may be associated with an increase in incompetent memory T cells and inflammatory cytokines produced by macrophages, whereas the defective clearance of amyloid-beta Aβ1–42 may be related to the defective transcription of immune genes necessary for phagocytosis, β-1,4-mannosyl-glycoprotein, 4-β-N-acetylglucosaminyltransferase, and Toll-like receptors. The approaches used for re-balancing Aβ immunity and inflammation are being pursued in animal models and the peripheral blood mononuclear cells of patients [ 179 , 181 , 182 , 183 ]. Increased inflammation may represent the “first hit” and defective transcription of immune genes represent the “second hit” in the pathogenesis of AD.…”
Section: Neurogenesis Is Stimulated By Vitamin D Metabolites and Smentioning
confidence: 99%
See 1 more Smart Citation